Superior Verbal Memory Outcome After Stereotactic Laser Amygdalohippocampotomy - Drane, Daniel L.; Willie, Jon T.; Pedersen, Nigel P.; Qiu, Deqiang; Voets, Natalie L.; Millis, Scott R.; Soares, Bruno P.; Saindane, Amit M.; Hu, Ranliang; Kim, Michelle S.; Hewitt, Kelsey C.; Hakimian, Shahin; et al. (Frontiers in Neurology, 2021)
Abstract Objective: To evaluate declarative memory outcomes in medically refractory epilepsy patients who underwent either a highly selective laser ablation of the amygdalohippocampal complex or a conventional open temporal lobe resection. Methods: Post-operative change scores were examined for verbal memory outcome in epilepsy patients who underwent stereotactic laser amygdalohippocampotomy (SLAH: n=40) or open resection procedures (n=40) using both reliable change index (RCI) scores and a 1-SD change metric. Results: Using RCI scores, patients undergoing open resection (12/40, 30.0%) were more likely to decline on verbal memory than those undergoing SLAH (2/40 [5.0%], p=0.0064, Fisher’s exact test). Patients with language dominant procedures were much more likely to experience a significant verbal memory decline following open resection (9/19 [47.4%]) compared to laser ablation (2/19 [10.5%], p=0.0293, Fisher’s exact test). 1 SD verbal memory decline frequently occurred in the open resection sample of language dominant temporal lobe patients with mesial temporal sclerosis (8/10 [80.0%]), although it rarely occurred in such patients after SLAH (2/14, 14.3%) (p=0.0027, Fisher’s exact test). Memory improvement occurred significantly more frequently following SLAH than after open resection. Interpretation: These findings suggest that while verbal memory function can decline after laser ablation of the amygdalohippocampal complex, it is better preserved when compared to open temporal lobe resection. Our findings also highlight that the dominant hippocampus is not uniquely responsible for verbal memory. While this is at odds with our simple and common heuristic of the hippocampus in memory, it supports the findings of non-human primate studies showing that memory depends on broader medial and lateral TL regions.